2006
DOI: 10.1002/pd.1519
|View full text |Cite
|
Sign up to set email alerts
|

Complete discrepancy between abnormal fetal karyotypes predicted by QF‐PCR rapid testing and karyotyped cultured cells in a first‐trimester CVS

Abstract: A chorion villus sample (CVS) biopsied at 11 weeks' gestation for raised nuchal translucency, revealed monosomy X (presumptive 45,X karyotype) by QF-PCR for rapid aneuploidy testing for chromosomes 13, 18, 21, X and Y. Long-term culture gave the karyotype: 47,XY,+ 21[66]/49,XYY,+ 21,+ 21 [22]. This discrepancy prompted redigestion of the combined residual villus fragments from the original QF-PCR assay. The repeat QF-PCR assay identified the presence of trisomy 21 and a Y chromosome consistent with a 47,XY,+ 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…Complete discrepancies are of greater concern; regarding AFs, there have been no reported complete discrepancies between a diagnostic QF‐PCR and karyotype result for autosomal trisomies although one group has reported a discrepant sex test result (XX on PCR, X/XXX on karyotype) . Diagnoses for CVS are more problematic, with reports of completely discrepant QF‐PCR and karyotype results due to placental mosaicism from a number of centres . The incidence of such discrepant results is likely to be determined by several factors, including the following: The quality and size of the original CV biopsy .…”
Section: Data Collections and Detection Ratesmentioning
confidence: 99%
“…Complete discrepancies are of greater concern; regarding AFs, there have been no reported complete discrepancies between a diagnostic QF‐PCR and karyotype result for autosomal trisomies although one group has reported a discrepant sex test result (XX on PCR, X/XXX on karyotype) . Diagnoses for CVS are more problematic, with reports of completely discrepant QF‐PCR and karyotype results due to placental mosaicism from a number of centres . The incidence of such discrepant results is likely to be determined by several factors, including the following: The quality and size of the original CV biopsy .…”
Section: Data Collections and Detection Ratesmentioning
confidence: 99%
“…QF-PCR can detect mosaicisms with low-level trisomy cell lines [19]. To date, only a few case reports of complete discrepancies between diagnostic QF-PCR and CVS karyotyping results for common selected autosomal trisomies of chromosomes 13, 18, and 21 have been reported [678920]. In the past, the incidence of true false-negative CVS results by short-term culture and LTC was estimated to be lower than 0.03% (1 in 3,300) [21].…”
Section: Discussionmentioning
confidence: 99%
“…QF-PCR has been widely used in most developed countries, but the efficacy of CVS with QF-PCR has not been validated in Korea. To date, only a few case reports of complete discrepancies between diagnostic QF-PCR and CVS karyotyping results for common selected autosomal trisomies of chromosomes 13, 18, and 21 have been described [6789] and there have been no reports on QF-PCR by CVS in Korea. Therefore, the primary outcome of this study was the detection rate of the common aneuploidies with trisomies 13, 18, and 21 by QF-PCR via CVS.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that QF-PCR cannot detect mosaicism at a level lower than 15%, which is rarely the case when full cytogenetic analysis is performed in LTC [4,27] . In our study the discrepancies between the QF-PCR and LTC results in the cases of mos +21, ( table 3 ; cases 1 and 2) and mos 45,X/46,XY ( table 3 ; case 3) could be attributed to sampling from different sites of a mosaic placenta and testing or culturing different cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…A complete discrepancy in the prediction of fetal trisomies 18 and 21 in CVS by QF-PCR analysis of uncultured villi and karyotyping after LTC is rare, but it has been reported in certain cases [26][27][28][29] . It has also been shown that QF-PCR cannot detect mosaicism at a level lower than 15%, which is rarely the case when full cytogenetic analysis is performed in LTC [4,27] .…”
Section: Discussionmentioning
confidence: 99%